Pacing parameters and success rates of permanent His-bundle pacing in patients with narrow QRS: a single-centre experience. Issue 5 (15th December 2018) - Su, Lan; Wu, Shengjie; Wang, Songjie; Wang, Zhengxian; Xiao, Fangyi; Shan, Peiren; Zhou, Hao; Huang, Zhouqing; Xu, Lei; Huang, Weijian
Abstract: Aims: High and unstable capture thresholds affect the success rate of permanent His-bundle pacing (HBP). We aimed to introduce the modified techniques during different periods and the corresponding success rate of HBP implantation. Methods and results: Patients from a single centre who had intrinsic QRS < 120 ms and HBP attempts were included in the study. The success rate and pacing parameters were described for three periods based on procedural modifications, i.e. Stage 1 using the conventional HBP procedure (August 2012 to May 2013), Stage 2 with addition of the dual-lead method (June 2013 to October 2014), and Stage 3 with the further addition of stability assessment during fixation (November 2014 to October 2016). The patients with successful permanent HBP were followed. A total of 310 patients were included with the average age of 70.3 ± 10.7 years. The success rate of acute HBP was 84.85%, 98.3%, and 99.20% during Stages 1–3, respectively ( P  < 0.001). The permanent HBP implantation rates increased from 77.3% during Stage 1 to 85.7% during Stage 2 and 89.6% during Stage 3 ( P  = 0.07). The acute His-bundle capture threshold reduced from 1.30 ± 0.7 V/0.5 ms during Stage 1 to 1.11 ± 0.6 V/0.5 ms during Stage 2 and further to 0.85 ± 0.51 V/0.5 ms during Stage 3 ( P  < 0.001). At the 12-month follow-up, the mean change in the HBP threshold decreased from 0.60 ± 0.59 V/0.5 ms during Stage 1 to 0.33 ± 0.39 V/0.5 ms during Stage 3 ( P  = 0.002). Conclusion: The HBP implantation success rate, pacing threshold, and its stability during follow-up were improved by using the dual-lead method and stability assessment techniques.